EvaGreen-based real-time PCR assay for sensitive detection of salmonid alphavirus. (June 2018) - Shi, Wen; Wang, Yuting; Ren, Xuanyu; Gao, Shuai; Hua, Xiaojing; Guo, Mengting; Tang, Lijie; Xu, Yigang; Ren, Tong; Li, Yijing; Liu, Min
Abstract: Salmonid alphaviruses (SAVs), which include the etiological agents of salmon pancreas disease (PD) and sleeping disease (SD), are significant viral pathogens of European salmonid aquaculture, resulting in substantial economic losses to the salmonid-farming industry. Even though many countries including China have not reported the presence of SAV infections, these countries may be seriously threatened by these diseases as the salmon fish import trade increases. Thus, it is indeed necessary to develop efficient detection methods for the diagnosis and prevention of SAV infection. Real-time PCR assays have been increasingly used in viral detection, and in many cases scientists prefer dye-based real-time PCR assays for their high sensitivity and low cost. In this study, we developed a novel, sensitive, low-cost detection method, EvaGreen-based real-time PCR assay for the detection of SAV. This assay exhibited high specificity for SAV1, SAV2, and SAV5 and was able to detect SAV at concentrations as low as 1.5 × 10 1 copies, making them more sensitive than the approved conventional RT-PCR method (detection limit, 1.5 × 10 6 copies). Assessment of infected fish samples showed that the sensitivity of EvaGreen-based assay was higher than previously developed SYBR Green assay (227 assay). Thus, we report that the EvaGreen real-time PCR assays is an economical alternative diagnostic method for the rapid detection of SAV1, SAV2, and SAV5 infection, providing improved technical support for the clinical diagnosis and epidemiological investigation of SAV. Highlights: A low-cost and sensitive EvaGreen-based real-time PCR assay for SAV was developed. This assay is suitable for the diagnosis of SAV infection in high-throughput clinical samples. This assay could be used for simultaneous detection of different subtypes of SAV in infected fish.